2019
DOI: 10.1177/1533033819886899
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Radiogenic Second Cancer Based on Differential DVH: Central Nervous System Malignant Tumor in Children

Abstract: Objectives:To quantify the risk of radiogenic second cancer in pediatric patients receiving hippocampal-sparing craniospinal irradiation either with intensity-modulated radiation therapy or tomotherapy due to the development of a solid second cancer after radiotherapy using the concept of excess absolute risk.Methods:Computed tomography images of 15 pediatric patients who received craniospinal irradiation treatment were selected for this study. For each case, intensity-modulated radiation therapy and tomothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Other authors have mostly reported on a smaller number of brain OARs, with focus on optic nerves, chiasm, brainstem, and hippocampi ( Supplementary material - Figure S5 ) [15] , [17] , [19] , [25] , [26] , [27] , [28] , [29] , [30] . There is limited data reporting on MRI-based auto-segmentation in the brain, as most of the reports are CT-oriented [16] , [18] , [31] , [32] , [33] , [34] , [35] , [36] , [37] . Nonetheless, some OARs (Cochlea, Eyes, Retina, and Lenses) are not included in this model and are of high importance for radiotherapy planning and would require manual delineation.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have mostly reported on a smaller number of brain OARs, with focus on optic nerves, chiasm, brainstem, and hippocampi ( Supplementary material - Figure S5 ) [15] , [17] , [19] , [25] , [26] , [27] , [28] , [29] , [30] . There is limited data reporting on MRI-based auto-segmentation in the brain, as most of the reports are CT-oriented [16] , [18] , [31] , [32] , [33] , [34] , [35] , [36] , [37] . Nonetheless, some OARs (Cochlea, Eyes, Retina, and Lenses) are not included in this model and are of high importance for radiotherapy planning and would require manual delineation.…”
Section: Discussionmentioning
confidence: 99%